Changes in soil organic carbon pools after 15 years of Conservation Agriculture in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system of eastern Indo-Gangetic plains - Mahala, Deep Mohan; Meena, Mahesh Chand; Dwivedi, Brahma S.; Datta, Siba Prasad; Dey, Abir; Das, Debarup; Parihar, Chiter Mal; Yadav, R.K.; Chaudhary, Amresh; Jat, Raj Kumar; Choudhary, Kajod Mal; Gathala, Mahesh Kumar; et al. (Indian Council of Agricultural Research, 2023)
The present study was carried out at Dr. Rajendra Prasad Central Agricultural University, Samastipur, Bihar during 2021-2023 to focus on examining alterations in SOC pools resulting from conservation agriculture (CA) practices in R-W system in the eastern IGP, following the collection of soil samples from a long-term trial that was initiated in rainy (kharif) season 2006. The trial included eight combinations, namely: conventional tilled rice (Oryza sativa L.) and wheat (Triticum aestivum L.) (CTR-CTW); CT rice and zero till wheat (CTR-ZTW); direct seeded rice (DSR) and wheat on permanent raised beds (PBDSR-PBW); ZTDSR and CT Wheat (ZTDSR-CTW); ZTDSR and ZT wheat without residue (ZTDSR-ZTW-R); ZTDSR-ZT wheat with residue (ZTDSR-ZTW +R); unpuddled transplanted riceZTW (UpTR-ZTW) and ZTDSR-sesbania brown manure-ZTW (ZTDSR-S-ZTW). Results revealed that implementing zero tillage (ZT) combined with residue retention in rice and wheat cultivation led to enhanced levels of soil organic carbon (SOC) across all four fractions, namely very labile (CVL), labile (CL), less labile (CLL), and non-labile (CNL), in comparison to the continuous and rotational tillage practices. The tillage and residue management options significantly affected the lability index (LI) and C pool index (CPI), with zero-tillage and residue retention leading to lower LI and higher CPI values. The management practices significantly affected the C management index (CMI), with zero-tillage and residue retention showing the highest CMI values. Findings showed the potential of CA practices for enhancing soil C quality as well as C sequestration in soil of the Eastern IGP of India.